Synthesis and Structure of Two Supramolecular Compounds Based on Macrocyclic Nickel(II) Complex and [Mo8O26]4- - Huang, Zhong-Wen; Pan, Ze-Yi; Zhou, Dong-Lai; Ou, Guang-Chuan (Asian Journal of Chemistry, 2015)
Two supramolecular structures with the formula [NiL]2[Mo8O26]·2H2O (1) and [NiL][Na2Mo8O26] (2) (L = 5,5,7,12,12,14-hexamethyl-1,4,8,11-tetraazacyclotetradecane) were synthesized and characterized by elemental analyses and IR spectra. The crystal structures were determined by the X-ray diffraction. The crystal of complex 1 is orthorhombic: space group Pbca, a = 17.812 (2), b = 15.942 (2), c = 19.295 (3) Å, V = 5478.8(12) Å3, Z = 4. The crystal of complex 2 is triclinic: space group P-1, a = 10.022(19), b = 10.717(2), c = 11.110(2) Å, a = 87.930(3)°, b = 72.115(3)°, g = 62.383(3)°, V = 998.2(3) Å3, Z = 1. In both complexes, the [NiL]2+ and [Mo8O26]4- monomers are connected through intermolecular hydrogen bonding to generate two-dimensional sheets.